1989
DOI: 10.1111/j.1440-1681.1989.tb01549.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Actions of Human Endothelin in Conscious Sheep

Abstract: 1. Synthetic human endothelin was injected intravenously over the range 1.5-50 micrograms to examine its cardiovascular actions in conscious sheep. 2. Mean arterial pressure increased by 9-21 mmHg within 30-120 s over the range 5-50 micrograms endothelin. The increase in blood pressure was associated with increased calculated total peripheral resistance and a fall in cardiac output and heart rate. Stroke volume was increased. 3. Injection of endothelin into ganglion blocked sheep produced vasoconstriction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
1995
1995

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…The sustained reduction in cardiac output observed in the present study is consistent with the short-term actions of endothelin in rats (Han et al 1989b) and sheep (Scoggins et al 1989). Endothelin has been reported to have a positive inotropic effect on the isolated heart (Ishikawa et al 1988), hence the fall in cardiac output may be reflex mediated in response to the increased blood pressure, or result from a direct constrictor action of endothelin on the coronary vasculature to reduce cardiac blood flow, or both.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The sustained reduction in cardiac output observed in the present study is consistent with the short-term actions of endothelin in rats (Han et al 1989b) and sheep (Scoggins et al 1989). Endothelin has been reported to have a positive inotropic effect on the isolated heart (Ishikawa et al 1988), hence the fall in cardiac output may be reflex mediated in response to the increased blood pressure, or result from a direct constrictor action of endothelin on the coronary vasculature to reduce cardiac blood flow, or both.…”
Section: Resultssupporting
confidence: 91%
“…When injected as an intravenous bolus, endothelin-1 produces a long lasting pressor response sustained for up to 1 h . We have previously shown that bolus injection of human endothelin-1 produces potent vasoconstriction in sheep (Scoggins et al 1989), but there is little information on the effects of long-term endothelin infusion. The aim of the present study was to define the cardiovascular effects of 24 h infusion of human endothelin-1 in conscious sheep.…”
Section: Introductionmentioning
confidence: 99%
“…In the cited studies, much higher doses were administered by bolus injection Wright & Fozard, 1989). The initial fall in blood pressure in those studies might be accounted for by decreased cardiac output and heart rate following a rapid increase in plasma endothelin concentrations (Goetz et al 1988;Scoggins, Spence, Parks, McDonald, Wade & Coghlan, 1989). In contrast, in the present study low concentrations of endothelin (approximately 0 4-4 pmol min-1) were infused over long periods thereby avoiding the development of transient high concentrations of the peptide.…”
Section: Discussionmentioning
confidence: 63%